Human-centered performance management in manual assembly – The impact of gamified KPI provision on performance and motivation. Issue 1 (2nd January 2023) - Ohlig, Jasmin; Hellebrandt, Thomas; Pötters, Patrick; Heine, Ina; Schmitt, Robert H.; Leyendecker, Bert
ABSTRACT: This paper presents results from an empirical study that investigates the effect of human-centered performance management concerning operational performance and work motivation of shop floor employees. The approach is based on gamified information provisioning. To date, the concept of gamification has been applied in numerous fields, yet hardly any related work provides empirical findings for the production environment. The approach is realized as an MES (Manufacturing Execution System) application and integrated into a business game simulation. The study design builds on an application scenario in manual assembly. Three treatment groups were defined for investigation. The developed business game was conducted among 150 trainees in technical vocational schools in Germany. The obtained data is evaluated concerning operational performance and motivation using descriptive statistics. Quantitative and qualitative observations show that the provision of gamified metrics-based information proves to be a motivation driver.